Editorial: Responsible well-being — a personal agenda for development - Chambers, Robert (World Development, 1997)
If development means good change, questions arise about what is good, and what sorts of change matter. Answers can be personally defined and redefined. The changing words, meanings and concepts of development discourse both reflect and influence what is done. The realities of the powerful tend to dominate. Drawing on experience with participatory approaches and methods which enable poor and marginalized people to express their realities, responsible well-being is proposed as a central concept for a development agenda. This links with capabilities and livelihoods, and is based on equity and sustainability as principles. The primacy of personal actions and non-actions in development points to the need for a pedagogy for the non-oppressed. This includes self-critical awareness, thinking through the effects of actions, and enabling those with power and wealth to experience being better off with less. Others are invited and encouraged to reflect, improve on this analysis, and write their own agenda.
Keywords: development vocabulary; ethics; methods; participation; poverty; well-being

PRA five years later - where are we now? / DRP - Cinco años después, ¿dónde nos encontramos? - Chambers, Robert; Guijt, Irene (Forest, Trees and People Newsletter, 1995)
PRA five years later: where are we now?

Guidelines for Drawing Causal Loop Diagrams - Daniel H., Kim (The Systems Thinker, 1992)
The old adage “if the only tool you have is a hammer, everything begins to look like a nail” can also apply to language. If our language is linear and static, we will tend to view and interact with our world as if it were linear and static. Taking a complex, dynamic, and circular world and linearizing it into a set of snapshots may make things seem simpler, but we may totally misread the very reality we were seeking to understand. Making such inappropriate simplifications “is like putting on your brakes and then looking at your speedometer to see how fast you were going” says Bill Isaacs of the MIT Center for Organizational Learning. Articulating Reality Causal loop diagrams provide a language for articulating our understanding of the dynamic, interconnected nature of our world. We can think of them as sentences which are constructed by linking together key variables and indicating the causal relationships between them. By stringing together several loops, we can create a coherent story about a particular problem or issue.

Learning and not learning from experience in rural project planning - Hulme, David (Public Administration and Development, 1989)
The theme of learning from experience as a means of improving the effectiveness of rural development projects and programmers has been common in recent years. Considerable effort has been put into refining, monitoring and evaluation systems to enhance organizational learning processes. However, an emphasis on normative approaches to evaluation and learning from experience has led to the neglect of research into the actual processes by which rural development agencies utilize experience. The case study presented here points to the shortcomings of such approaches and illustrates the partisan manner in which individuals and organizations treat the lessons of experience. Actively ‘not learning from experience’ is as much a part of organizational processes as learning from experience. This paper examines the implications of this finding and reviews alternative approaches to improving experiential learning in rural development activities. It is found that such a perspective does not generate the innocuous technical prescriptions characteristic of conventional approaches, but a number of useful directions for further research can be identified.

The Environment and Disease: Association or Causation? - Hill, Austin Bradford (Proceedings of the Royal Society of Medicine, 1965)